Case report: Persistent ST-segment elevation due to cardiac metastasis from lung cancer - Zhou, Jiawei; Zhan, Chengchuang; Zhou, Jing; Wei, Chao; Zou, Cao (Frontiers in Cardiovascular Medicine, 2023)
Patients with secondary cardiac cancer occasionally show ST segment elevation that mimics acute coronary syndrome, despite the absence of coronary artery occlusion. We herein describe a rare case of secondary cardiac cancer that presented with ST segment elevation. An 82-year-old Chinese man was admitted to the hospital with chest discomfort. Electrocardiography (ECG) showed ST segment elevation in the precordial leads and low-voltage QRS complexes in limb leads without development of Q waves. Unexpectedly, emergency coronary angiography showed no significant stenosis on coronary arteries. But fortunately, Transthoracic Echocardiography (TTE) revealed massive pericardial effusion and a mass at the apex of ventricular myocardium. Coincidentally, contrast-enhanced chest computed tomography showed primary lung cancer in the left lower lobe, pericardial effusion, and myocardial metastasis at the ventricular apex. The pericardiac fluid was bloody with significantly increased CEA level and exfoliated tumor cells. The lung histopathological report suggested squamous cell carcinoma. Two months later, this patient died. These findings suggested that the persistent ST segment without development of Q waves was associated with the ventricular invasion by primary lung cancer and may indicate a poor prognosis. In conclusion, physicians should be aware of persistent ST segment elevation mimicking myocardial infarction due to cardiac metastasis with a poor prognosis.